2015
DOI: 10.3115/v1/w15-14
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings of the Third Workshop on Metaphor in NLP

Abstract: ii IntroductionCharacteristic to all areas of human activity (from poetic to ordinary to scientific) and, thus, to all types of discourse, metaphor becomes an important problem for natural language processing. Its ubiquity in language has been established in a number of corpus studies and the role it plays in human reasoning has been confirmed in psychological experiments. This makes metaphor an important research area for computational and cognitive linguistics, and its automatic identification and interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Despite progress on automatic recognition of metaphors (e.g. Veale 2016, Shutova et al 2015, Chakrabarty et al 2021, the kind of detail shown here is generally not retrievable computationally. Lane Lawley and Lenhart Schubert generate"Logical Story Representations via FrameNet + Semantic Parsing".…”
Section: Introduction To the Workhopmentioning
confidence: 91%
“…Despite progress on automatic recognition of metaphors (e.g. Veale 2016, Shutova et al 2015, Chakrabarty et al 2021, the kind of detail shown here is generally not retrievable computationally. Lane Lawley and Lenhart Schubert generate"Logical Story Representations via FrameNet + Semantic Parsing".…”
Section: Introduction To the Workhopmentioning
confidence: 91%